The frequency and antibiotic sensitivity patterns of uropathogens isolated from urinary tract infection patients in Basra (Iraq) - Alassadi, N. M.; Al-Ghizzawi, G. J. (Regulatory Mechanisms in Biosystems, 2025)
Urinary tract infections (UTIs) are common across both sexes and age demographics, resulting from bacterial infection of the urinary system, and their severity has intensified due to the increase in bacterial resistance to antibiotics. This study aimed to isolate and identify the causes of UTI in Basra, Iraq, and to clarify their antibiotic resistance pattern. 140 mid-stream urine sa m ples were collected from patients with symptoms of infection at Al Fayha Teaching Hospital and Al-Sadr Teaching Hospital. The bacterial strains were identified biochemically and confirmed using the VITEK system, which was used to detect the ant i biogram pattern of bacterial identification. Of the 140 samples collected from November 2022 to March 2023, 101 samples showed positive growth. The infection rate among females (55.3%) was higher than males (44.6%), with no significant diffe r ences. Females showed higher infection rates than males across all age groups, except for individuals over 60 years of age, where the proportion of infected males exceeded that of females. The present investigation revealed that the predominant gram-positive bacterium was Staphylococcus aureus , with a frequency of 25. 7 %, followed by Staphylococcus epidermidis at 18. 4 %. Among the Gram-negative bacteria, E scherichia coli (23. 9 %) was the predominant species, followed by Pseudomonas aerug i nosa (11.9%). The majority of gram-positive isolates were resistant to cefoxitin, benzylpenicillin, oxacillin, erythromycin, and fusidic acid. Gram-negative bacteria exhibit elevated resistance to ticarcillin, piperacillin, and ciprofloxacin. S. aureus was the predominant isolate, and linezolid, nitrofurantoin, and tigecycline were identified as the most efficacious antibiotics against gram-positive bacteria, with 100% sensitivity.